Investigation of Research impacts on the Zika Virus - An Approach Focusing on Social network Analysis and Altmetrics - Maia, Luís Fernando Monsores Passos; Oliveira, Jonice (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2017: Proceedings of the 23rd Brazilian Symposium on Multimedia and the Web, 2017)
Zika has drawn international attention in 2015, both for its epidemic proportion and its consequences. Scientific advances are made, but is the population aware? Allow the population to understand the scientific advances of a disease, achievements made and current risk situation is important to avoid panic, prejudice and violence. This work1 aims to study the impact of the main Zika researchers and the repercussion of their research on population. For this purpose, the main researchers were identified in co-authorship networks and, through altmetric indexes (alternative metrics), the repercussion of these researchers were analyzed in news and social media.